Reexamination of the Embolic Stroke of Undetermined Source Concept. Issue 8 (1st July 2021) - Albers, Gregory W.; Bernstein, Richard; Brachmann, Johannes; Camm, A. John; Fromm, Peter; Goto, Shinya; Granger, Christopher B.; Hohnloser, Stefan H.; Hylek, Elaine; Krieger, Derk; Passman, Rod; Pines, Jesse M.; et al.
Abstract : Occult atrial fibrillation (AF) is a leading cause of stroke of unclear cause. The optimal approach to secondary stroke prevention for these patients remains elusive. The term embolic stroke of undetermined source (ESUS) was coined to describe ischemic strokes in which the radiographic features demonstrate territorial infarcts resembling those seen in patients with confirmed sources of embolism but without a clear source of embolism detected. It was assumed that patients with ESUS had a high rate of occult AF and would benefit from treatment with direct oral anticoagulants, which are at least as effective as vitamin K antagonists for secondary stroke prevention in patients with AF, but with a much lower risk of intracerebral hemorrhage. Two recent large randomized trials failed to show superiority of direct oral anticoagulants over aspirin in ESUS patients. These findings prompt a reexamination of the ESUS concept, with the goal of improving specificity for detecting patients with a cardioembolic cause. Based on the negative trial results, there is renewed interest in the role of long-term cardiac monitoring for AF in patients who fit the current ESUS definition, as well as the clinical implication of detecting AF. Ongoing trials are exploring these questions. Current ESUS definitions do not accurately detect the patients who should be prescribed direct oral anticoagulants, potentially because occult AF is less common than expected in these patients and/or anticoagulants may be less beneficial in patients with ESUS but no AF than they are for patients with stroke with established AF. More specific criteria to identify patients who may be at higher risk for occult AF and reduce their risk of subsequent stroke have been developed and are being tested in ongoing clinical trials.